2010
DOI: 10.1186/1472-6947-10-24
|View full text |Cite
|
Sign up to set email alerts
|

Modeling screening, prevention, and delaying of Alzheimer's disease: an early-stage decision analytic model

Abstract: BackgroundAlzheimer's Disease (AD) affects a growing proportion of the population each year. Novel therapies on the horizon may slow the progress of AD symptoms and avoid cases altogether. Initiating treatment for the underlying pathology of AD would ideally be based on biomarker screening tools identifying pre-symptomatic individuals. Early-stage modeling provides estimates of potential outcomes and informs policy development.MethodsA time-to-event (TTE) simulation provided estimates of screening asymptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…The available validated diagnostics for AD are neither scalable for mass population screening nor sufficiently cost-effective to be practical [ 19 ]. For example, brain imaging can provide clear evidence of neurodegeneration but is restricted to specialist centers [ 20 ] and an imaging-based public health screening program would not be affordable [ 19 , 21 ]. There is a pressing need to stratify the older healthy population, using simple and cost-effective methods, to, for example, identify those appropriate to enrich clinical trials of novel AD treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The available validated diagnostics for AD are neither scalable for mass population screening nor sufficiently cost-effective to be practical [ 19 ]. For example, brain imaging can provide clear evidence of neurodegeneration but is restricted to specialist centers [ 20 ] and an imaging-based public health screening program would not be affordable [ 19 , 21 ]. There is a pressing need to stratify the older healthy population, using simple and cost-effective methods, to, for example, identify those appropriate to enrich clinical trials of novel AD treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The use of biomarkers for identification of individuals with AD prior to the appearance of clinical symptoms, the socalled pre-dementia phase of the disease [2], will be essential to the development of drugs for early intervention [3][4][5]. Furthermore, if sufficiently powered, some biomarkers could be used as part of a screening program for at-risk elderly people [6].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment effectiveness of ChEIs for MCI patients was derived from a recent Cochrane review study [ 36 ] where authors reported evidence of minor benefits (effects for year 1 and year 3 were borderline significant; effects for year 2 were significant) with limitations and uncertainty, and further concluded that ChEI treatment is not recommended for MCI patients due to weak evidence. Compared with other similar studies using a hypothetical treatment effectiveness (RR 0.5) [ 29 31 , 70 , 71 , 73 ], however, our assumption was relatively conservative (RR 0.84) and was based on point estimates reported from the most recent review evidence. Moreover, by applying the empirical data, our approach should better reflect what the real potential treatment benefits might be, acknowledge the debate of whether we should treat MCI patients or not based on the current evidence, and reflect that if a decision must be made, it should be made based on the available evidence [ 38 ].…”
Section: Discussionmentioning
confidence: 99%